THE INFLUENCE OF TASTE, PRICE AND LOCATION ON PURCHASING DECISIONS AT AA SEBLAK STALL IN TEBING TINGGI CITY - Nila Sahliana; Tiara Afrillia; Ari Syahputra; Frederik Rudy Sentosa Rajagukguk (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze and determine the influence of taste, price, and location on purchasing decisions at Warung Seblak AA in Tebing Tinggi City. This type of research is quantitative. The population in this study were consumers of Warung Seblak AA in Tebing Tinggi City with sampling using a purposive sampling technique. The data collection method was carried out using a questionnaire. Hypothesis testing used multiple linear regression analysis. The results of this study indicate that partially, Taste, Price, and Location each have a positive influence on Purchasing Decisions. SimultaneouslyThe three variables together have a significant influence on purchasing decisions.